2014
DOI: 10.1371/journal.pone.0085721
|View full text |Cite|
|
Sign up to set email alerts
|

Simvastatin Inhibits Glucose Metabolism and Legumain Activity in Human Myotubes

Abstract: Simvastatin, a HMG-CoA reductase inhibitor, is prescribed worldwide to patients with hypercholesterolemia. Although simvastatin is well tolerated, side effects like myotoxicity are reported. The mechanism for statin-induced myotoxicity is still poorly understood. Reports have suggested impaired mitochondrial dysfunction as a contributor to the observed myotoxicity. In this regard, we wanted to study the effects of simvastatin on glucose metabolism and the activity of legumain, a cysteine protease. Legumain, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…It seems however that this is not the only mechanism of toxicity, and some authors propose other ways which would also be involved in geranylgeranyl pyrophosphate, cell apoptosis and dysfunction in glucose oxidation [49,50] . Some studies have linked this muscular toxicity with muscle weakness [51,52] .…”
Section: Statinsmentioning
confidence: 99%
“…It seems however that this is not the only mechanism of toxicity, and some authors propose other ways which would also be involved in geranylgeranyl pyrophosphate, cell apoptosis and dysfunction in glucose oxidation [49,50] . Some studies have linked this muscular toxicity with muscle weakness [51,52] .…”
Section: Statinsmentioning
confidence: 99%
“…Statins were shown to inhibit GLUT4 expression and glucose uptake in adipocytes [9][10][11][12]. In muscle cells, simvastatin was also reported to decrease glucose uptake [13,14], but no change in GLUT4 protein expression was observed [28].…”
Section: Introductionmentioning
confidence: 99%
“…Caveolin‐1, a scaffolding protein and the principal component of the caveolae , affects hepatic lipid homeostasis . A recent study showed that treatment with simvastatin, a HMG‐CoA reductase inhibitor, decreased the mature form and activity of legumain . Moreover, we showed that knockdown of AACS in the liver of mice lowers the serum cholesterol concentration .…”
Section: Discussionmentioning
confidence: 61%